Diagnostic Efficacy of CT/MR Imaging and Adrenal Vein Sampling for Localization of Aldosterone-producing Adrenal Adenomas in Primary Aldosteronism - Boontankan, Nontika; Sasiwimonphan, Kewalee (The ASEAN Journal of Radiology, 2019)
Objective: To test the sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) of CT/MR imaging and adrenal vein sampling (AVS) for diagnosis of aldosterone-producing adrenal adenoma (APA). Material and method: Retrospective study of 14 patients with primary hyperaldosteronism (PAL) who underwent both CT/MR imaging and AVS between June 2007 and June 2012 were performed. The study included 7 male and 7 female patients. Review CT/MR findings of these cases and compared with AVS results were done. Results: Five of fourteen patients (35%) had unilateral adrenal nodules on CT, and one of fourteen patients (7.1%) had bilateral adrenal nodules on CT[D1]. The remaining eight patients had no significant nodules in both adrenal glands. Among 5 patients who had unilateral adrenal nodule detected from CT, 4 patients (80%) with nodule greater than 10 mm also presented with lateralization from AVS and finally pathological proven APA. The last patient with unilateral nodule showed small size less than 10 mm and had AVS results of bilateral lesion. Medical therapy was applied for this patient instead of surgical treatment. In other group (8 of 14 patients, 57.1%), there was no significant nodule from CT or MRI and AVS results indicated bilateral lesions in two patients (25%). The rest of six patients found unilateral lesion on AVS which underwent adrenalectomy and histological revealed adrenal hyperplasia of all cases. Two of six patients concluded to be primary adrenal hyperplasia (PAH) or unilateral adrenal hyperplasia (UAH), which showed clinical cure after adenalectomy. The remaining four patients who showed no improvement of hypertension after adrenalectomy concluded to be bilateral adrenal hyperplasia (BAH). The sensitivity, specificity, accuracy, PPV and NPV for detected adrenal adenoma by CT/MRI of our study were 66.67%, 87.50%, 78.57%, 80.00%, and 77.78%, respectively. The sensitivity, specificity, accuracy, PPV and NPV for detected adrenal adenoma by AVS at cut point AVS ratio at 2 were 100%, 50%, 71.43%, 60% and 100%, respectively. Conclusion: In patient with suspected PAL who presented with unilateral adrenal nodule at least 10 mm in size detected by CT, these patient should be referred for adrenalectomy without need to performing AVS. The differentiation of subtype in patients with PAL is most reliably achieved with AVS which may reserve for patient who had no significant adrenal nodule from CT/MRI.